2011
DOI: 10.1007/s12613-011-0405-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of high performance and high strength heavy concrete for radiation shielding structures

Abstract: Heavy concrete currently used for construction contains special materials that are expensive and difficult to work with. This study replaced natural aggregate (stones) in concrete with round steel balls, which are inexpensive and easily obtainable. The diameters of the steel balls were 0.5 and 1 cm, and their density was 7.8 kg/m 3 . Dense packing mixture methods were used to produce heavy concrete with densities of 3500 and 5000 kg/m 3 . The various properties of this concrete were tested according to the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…[4][5][6][7][8][9]. Currently, heavy concretes used for construction works contain special costly fillers, such as barite, ilmenite, and Materials 2022, 15, 2925 2 of 20 magnetite [10][11][12]. Usually heavyweight aggregate contains a high content of metallic phases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8][9]. Currently, heavy concretes used for construction works contain special costly fillers, such as barite, ilmenite, and Materials 2022, 15, 2925 2 of 20 magnetite [10][11][12]. Usually heavyweight aggregate contains a high content of metallic phases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of waste particles as fillers can reduce the material quality of concretes. Thus, replacing some parts of natural aggregates with steel waste particles caused some reduction in strength [11]. It was shown that as the amount of steel waste increased, the workability of the concrete mixture became an important issue which eventually required larger amounts of water to achieve a minimum slump [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve high densities, some authors have analyzed nonstructural ferrous additions such as iron punchings [18,19] or electric arc furnace slags [12]. These additions considerably improve concrete attenuation coefficients [20].…”
Section: Introductionmentioning
confidence: 99%